Monocyte Function and Clinical Outcomes in Febrile and Afebrile Patients With Severe Sepsis. Issue 4 (October 2018) - Drewry, Anne M.; Ablordeppey, Enyo A.; Murray, Ellen T.; Dalton, Catherine M.; Fuller, Brian M.; Kollef, Marin H.; Hotchkiss, Richard S.
ABSTRACT: Introduction: Absence of fever is associated with higher mortality in septic patients, but the reason for this is unknown. Immune dysfunction may be a potential link between failure to mount a fever and poor outcomes. The purpose of this study was to evaluate monocyte function and clinical surrogates of immunity (i.e., mortality and acquisition of secondary infections) in febrile and afebrile septic patients. Methods: Single-center, prospective cohort study of 92 critically ill septic patients. Patients were categorized into febrile (≥38.0°C) and afebrile (<38.0°C) groups based on temperature measurements within 24 hours of sepsis diagnosis. HLA-DR expression and LPS-induced TNF-α production were quantified on days 1–2, days 3–4, and days 6–8 after sepsis diagnosis. A repeated measures mixed models analysis was used to compare these markers between the two groups. Results: Forty-four patients (47.8%) developed a fever within 24 h of sepsis diagnosis. There were no significant differences in HLA-DR expression or LPS-induced TNF-α production between febrile and afebrile patients at any individual time point. However, HLA-DR expression significantly increased between days 1–2 and days 6–8 (median difference 8118 [IQR 1, 662, 9, 878] antibodies/cell, P  = 0.002) in febrile patients, but not in afebrile patients (median difference 403 [−3, 382, 3, 507] antibodies/cell, P  = 0.25). Afebrile patients demonstrated higher 28-day mortality (37.5% vs 18.2%) and increased acquisition of secondary infections (35.4% vs. 15.9%). Conclusions: Absence of fever is associated with suppressed HLA-DR expression over time, a finding suggestive of monocyte dysfunction in sepsis, as well as worse clinical outcomes. Abstract : Supplemental Digital Content is available in the text